Implikasi penerapan protokol CHSE (cleanliness, health, safety and environment sustainability) dalam bidang akomodasi pada kapal pinisi di labuan bajo di era pandemi covid-19 - Sari, Retno Juwita; Juniarta, Pande Putu; Darma, I Putu Ryan (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 2 (2021): Vol.5,No.2,2021DO - 10.24843/JKH.2021.v05.i02.p01, 2022)
The pandemic that has occurred for almost two years has also changed the direction of tourism policy in Indonesia, the government is focusing on the tourism sector through the application of health protocols in a disciplined manner which is intensively carried out through various forms of socialization to the implementation of certification in various tourism business fields. Likewise Labuan Bajo, continues to strive to increase the confidence of tourists to come back by paying attention to health protocols in a disciplined manner. Kemenparekraf/Baparekraf took the initiative to develop CHSE-based health protocol guidelines in each tourism sector, including the accommodation sector. This is done considering that the CHSE-based health protocol has an important role to revive the tourism sector, especially in the accommodation sector. In this study, the researchers focused on the implications of implementing CHSE on phinisi tourist ships in Labuan Bajo. The results of the analysis of the application of CHSE are the success of the three ships in implementing the CHSE (Cleanliness, Health, Safety and Environmental Sustainability) concept even though they have not been certified CHSE by the Ministry of Tourism and Creative Economy. However, in the implementation of CHSE (Cleanliness, Health, Safety and Environmental Sustainability) all points in this application have health protocols that have met the criteria so that tourists can visit Labuan Bajo comfortably and safely by phinisi boat as the right choice of accommodation. Keywords : CHSE, Accommodation, Phinisi